MENINGKATKAN KESIAPSIAGAAN KELUARGA MELALUI SOSIALISASI DAN SIMULASI PENANGANAN GAWAT DARURAT ANAK DI LINGKUNGAN KELUARGA DI KOTA MAKASSAR - Hady J, Abd; Hariani, Hariani; Nur, Muhammad; Anggriani, Sri; AR, Masdiana; Rahman, Rahman (Jurnal Pengabdian Masyarakat Sabangka, 2025)
Child emergencies, such as seizures, choking, or shortness of breath, often occur suddenly and require a rapid response from families as first responders. However, according to data from the Makassar City Health Office (2024), most families lack the basic knowledge and skills to handle these situations. This community service activity aims to improve family preparedness through outreach and simulations of pediatric emergency management within families in Makassar City. The method used was a participatory approach through educational lectures, interactive discussions, and hands-on simulations for 45 housewives and childcare providers in Mamajang Dalam Village. The results showed a significant increase in participants' knowledge (78%) and basic first aid skills (65%) after the intervention. Group discussions revealed that the simulations helped participants feel more confident in dealing with emergency situations. This activity has proven effective in increasing family preparedness for pediatric emergencies. It is hoped that similar programs can be integrated into community education policies at the village level in Makassar City and other regions. Collaboration between health workers, cadres, and RT officials is key to the sustainability of this program.